Project Based Learning (PjBL): Strengthening Philanthropic Character Based on Local Wisdom Through Citizenship Courses - Irzal Anderson; Melisa Melisa; Siti Tiara Maulia; Sundari Utami (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2024)
The aim of this research is to develop a learning model based on Project Based Learning (PjBL) based on local wisdom by looking at strengthening the character of philanthropy in citizenship courses for students in the PIPS FKIP Jambi University department as well as testing the feasibility of the product and the level of effectiveness of the learning tools developed. This research uses a development research design that adopts the Dick & Carey model which includes preliminary, analysis, design, development and testing stages. The subjects of this research were students in classes R001 and R002, first semester, Citizenship Education Study Program, FKIP, Jambi University. Data collection techniques and instruments were carried out using observation, validation instruments, presentations and knowledge test questions. After development, the program is tested to assess its effectiveness and feasibility. This testing can be conducted through field trials, measuring participants' learning outcomes, and analyzing the feedback obtained. The results of the research can be concluded that the PjBL learning model based on local wisdom with strengthening philanthropy is suitable for use for learning. Based on the validator's assessment, this learning model has met content validity with a score of getting an assessment from the lecturer and team of examiners in the